2022
DOI: 10.1093/ee/nvac030
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution of Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) Across a Fruit and Tree Nut Agricultural Ecosystem

Abstract: The invasive brown marmorated stink bug, Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), is a mobile, polyphagous agricultural pest that feeds on a variety of plants. In orchard systems, seasonal monitoring of adults and nymphs in fruit and nut trees and noncrop host plants in surrounding habitat can be used to identify, in time and space, areas of high-density aggregations to develop targeted pest management strategies. We explored the spatiotemporal distribution of H. halys adults and nymphs and assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In the present study, trap capture was similar for H. halys adults in both woodland and pecan habitat, however, H. halys nymphs were oftentimes captured in higher numbers in woodlands compared to pecan. A separate study that took place at this site also found H. halys nymphs and adults were captured at the highest densities in peach and woodlands, followed by pecan (Grabarczyk et al 2022b). Like H. halys , C. hilaris has also been captured at high densities in both row crop and non-crop habitat in woodlands (Grabarczyk et al 2021b).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In the present study, trap capture was similar for H. halys adults in both woodland and pecan habitat, however, H. halys nymphs were oftentimes captured in higher numbers in woodlands compared to pecan. A separate study that took place at this site also found H. halys nymphs and adults were captured at the highest densities in peach and woodlands, followed by pecan (Grabarczyk et al 2022b). Like H. halys , C. hilaris has also been captured at high densities in both row crop and non-crop habitat in woodlands (Grabarczyk et al 2021b).…”
Section: Discussionmentioning
confidence: 74%
“…Like H. halys , C. hilaris has also been captured at high densities in both row crop and non-crop habitat in woodlands (Grabarczyk et al 2021b). Mixed prevalence for both woodland and crop habitats is exemplary of stink bugs species like C. hilaris and H. halys that feed and develop on a variety of non-crop hosts in woodlands or along woodland edges then later disperse into nearby host crops to continue their seasonal development in the agroecosystem (Tillman and Cottrell 2016, Grabarczyk et al 2022b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the invasion of the brown marmorated stink bug, Halyomorpha halys (Stål), in the southeastern United States, stink bug pest populations in agroecosystems may consist of a combination of H. halys and indigenous species. Halyomorpha halys is a pest in orchards, vegetables, field crops, vineyards, and ornamentals (Leskey et al 2012, Rice et al 2014, Leskey and Nielsen 2018, Grabarczyk et al 2022). In the United States, both H. halys adults and nymphs cause feeding punctures in seeds that lead to the destruction of seeds and pods (Nielsen et al 2011, Owens et al 2013, Rice et al 2014).…”
mentioning
confidence: 99%